Magnetotunelamento e tunelamento foto-assistido ressonante em multipoços quânticos - Gustavo Soares Vieira (1998)
This work is divided in three parts: An investigation of the electronic transport in a superlattice of thick barriers with the presence of Terahertz radiation. We looked for a resonant behavior of the radiation energy and the energy separation between the first two levels of the superlattice wells. We studied the changes in the transport mechanism when the population of the energy levels is altered by the radiation. We used Terahertz radiation to detect the change in the energy separation between the first two energy levels of the wells of the superlattice caused by the magnetic field applied parallel to the superlattice layers. Finally, we studied the magnetotransport in the same superlattice with the magnetic field applied perpendicular to the superlattice layers. Without Terahertz radiation, we found a strong dependence of the scattering mechanisms and the tunneling behavior on the magnetic quantization of the two-dimensional electron gas in the wells.